Interfering factors of the emergency and risk of infection by COVID-19. / Factores que interfieren en la emergencia y riesgo de infección por COVID-19. - ESPIRITU – MARTINEZ, Antony Paul; CASTRO – LLAJA, Lindomira (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The objective of the study was to analyze the factors that hinder submitting to the state of emergency due to COVID - 19 and their relationship in the risk of infection by Coronavirus in informal providers. The survey was used as the technique and two questionnaires as instruments of data collection, one alluding the factors that hinder submitting to the state of emergency for COVID-19 and the other that measured the risk of infection by coronavirus. The results demonstrate that 45.3% (24) of informal providers present a high risk of infection by Coronavirus. It is concluded that unfavorable management of the factors that hinder the state of emergency in informal providers exponentially increases the risk of infection by COVID-19. RESUMEN El objetivo de estudio fue analizar los factores que obstaculizan someterse al estado de emergencia por COVID – 19 y su relación en el riesgo de infección por Coronavirus en proveedores ambulantes. Se utilizó la encuesta como técnica y dos cuestionarios como instrumentos de recolección de datos, uno aludiendo a los de factores que obstaculizan someterse al estado de emergencia por COVID-19 y el otro que midió el riesgo de infección por coronavirus. Los resultados demuestran que el 45.3% (24) de proveedores ambulantes presenta riesgo alto de infección por Coronavirus. Se llegó a la conclusión que el manejo desfavorable de los factores que obstaculizan el estado de emergencia en los proveedores ambulantes incrementa de manera exponencial el riesgo de infección por COVID-19.